Servant Leadership Model Development for Finance Officers of the Royal Thai Army Second Region - Chaimayo, Tuschai; Boonbai, Sayan; Kittiporn, Lamai (Journal of Roi Et Rajabhat University, 2021)
The purposes of this research were to 1) investigate components of servant leadership, 2) construct and develop a model for developing servant leadership and 3) assess the effectiveness of a developed model for developing servant leadership of the finance officers of the royal thai army second region. The samples were 105 of the commissioned officers and 105 of noncommissioned officers total of 210 officers. The instruments for collecting data were an expert interview form, a servant leadership questionnaire, an evaluation and servant leadership development model form, a servant leadership assessment form and a customer satisfaction assessment form. Data were analyzed using percentage, mean and standard deviation. The findings were as follow : 1) The components of servant leadership of the finance officers involved six majors as follows: (1) the role-based service, (2) determination of development and empowerment of personnel, (3) participation and community building, (4) having good vision and communication, (5) listening and empathy and (6) humility and good human relations. As a whole, leadership operational conditions was a moderate level. 2) The model for developing servant leadership of the finance comprised (1) principles, (2) objectives, (3) procedures, (4) the development for each component and (5) follow-up and evaluation. 3) The results from assessment the effectiveness of the servant leadership development model for the finance officers found that (1) the model had an appropriateness as a whole at a high level, (2) servant leadership had changed significantly higher after the experiment with statistical significance at the level of .01, (3) overall satisfaction of service users towards the servant leadership behavior of the experimental group was at a high level and (4) the 2 weeks follow - up servant leadership was significantly higher than after the experiment leadership development model at the level of .01.